Effect of Regional Revenue and Balancing Funds on Regional Independence Moderated by Capital Expenditure in East Kalimantan - Warti, Kendro; Suharto, Rahcmad Budi; Roy, Juliansyah (CV. Publikasi Indonesia, 2025)
This study aims to analyze the effect of Regional Revenue (PAD) and Balancing Funds on Regional Financial Independence, with Capital Expenditure as a moderating variable in districts and cities across East Kalimantan Province from 2019 to 2024. Employing a quantitative approach with a causal-comparative design, this research uses panel data derived from secondary sources, specifically the Regional Budget Realization Reports (LRA) published by BPKAD and DJPK. The analytical method applied is Moderated Regression Analysis (MRA) using SPSS version 22.0 to test both the direct and moderating effects among variables. The results indicate that Regional Revenue (PAD) has a positive and significant effect on regional financial independence, suggesting that higher PAD enhances local fiscal capacity. In contrast, Balancing Funds have a negative and significant impact, implying that greater reliance on central government transfers diminishes fiscal independence. Capital Expenditure functions as a dual moderator: it weakens the positive effect of PAD on regional independence but strengthens the impact of Balancing Funds on fiscal capacity when allocated effectively. The study recommends that local governments prioritize the expansion of PAD sources through more efficient tax and retribution management. Additionally, the effective and productivity-oriented allocation of capital expenditure should be emphasized to enhance long-term regional fiscal independence.